Speech Processing as a Far-Transfer Gauge of Serious Games for Cognitive Training in Aging: Randomized Controlled Trial of Web-Based Effectivate Training - Gal Nitsan; Shai Baharav; Dalith Tal-Shir; Vered Shakuf; Boaz M Ben-David (JMIR Publications, 2022)
BackgroundThe number of serious games for cognitive training in aging (SGCTAs) is proliferating in the market and attempting to combat one of the most feared aspects of aging-cognitive decline. However, the efficacy of many SGCTAs is still questionable. Even the measures used to validate SGCTAs are up for debate, with most studies using cognitive measures that gauge improvement in trained tasks, also known as near transfer. This study takes a different approach, testing the efficacy of the SGCTA-Effectivate-in generating tangible far-transfer improvements in a nontrained task-the Eye tracking of Word Identification in Noise Under Memory Increased Load (E-WINDMIL)-which tests speech processing in adverse conditions. ObjectiveThis study aimed to validate the use of a real-time measure of speech processing as a gauge of the far-transfer efficacy of an SGCTA designed to train executive functions. MethodsIn a randomized controlled trial that included 40 participants, we tested 20 (50%) older adults before and after self-administering the SGCTA Effectivate training and compared their performance with that of the control group of 20 (50%) older adults. The E-WINDMIL eye-tracking task was administered to all participants by blinded experimenters in 2 sessions separated by 2 to 8 weeks. ResultsSpecifically, we tested the change between sessions in the efficiency of segregating the spoken target word from its sound-sharing alternative, as the word unfolds in time. We found that training with the SGCTA Effectivate improved both early and late speech processing in adverse conditions, with higher discrimination scores in the training group than in the control group (early processing: F1,38=7.371; P=.01; ηp2=0.162 and late processing: F1,38=9.003; P=.005; ηp2=0.192). ConclusionsThis study found the E-WINDMIL measure of speech processing to be a valid gauge for the far-transfer effects of executive function training. As the SGCTA Effectivate does not train any auditory task or language processing, our results provide preliminary support for the ability of Effectivate to create a generalized cognitive improvement. Given the crucial role of speech processing in healthy and successful aging, we encourage researchers and developers to use speech processing measures, the E-WINDMIL in particular, to gauge the efficacy of SGCTAs. We advocate for increased industry-wide adoption of far-transfer metrics to gauge SGCTAs.